Didactic Engineering in the Development of Numerical Thinking (2020)
The development of numerical thinking in primary education is an important aspect of children’s mathematical training, since it allows for a general understanding of numbers and operations in order to facilitate the development of their handling and application. The work allows the implementation of a pedagogical strategy based on didactic engineering, which allows students to identify and formulate questions related to the management and understanding of numbers and their basic operations together with the decision to approach individually and which ones in a group way while planning and making decisions in their development and evaluation of results. The study is framed in the quantitative paradigm, in a quasi-experimental design, working with control and experimental groups. Pre-test is applied to identify the development of numerical thinking in students and as a support to the design of the intervention proposal. Once the proposal is developed, it is evaluated by means of a post-test that allows identifying significant improvements in the numerical thinking of the children of the experimental group in comparison with those of the control group. This leads to the conclusion that the developed intervention contributes favorably to the development of numerical thinking in children